How do women with lupus manage fatigue? A focus group study. Issue 8 (August 2016) - Kier, Anne; Midtgaard, Julie; Hougaard, Karin; Berggreen, Anja; Bukh, Gunhild; Hansen, Renata; Dreyer, Lene
Abstract Objective Half of patients with systemic lupus erythematosus (SLE) consider fatigue to be the most disabling disease symptom. To develop and promote strategies to prevent and control fatigue, this study aimed to describe how women with SLE manage the experience of fatigue. Methods Four focus groups were conducted with 27 women with SLE, and data were analyzed by means of framework analysis. Two patient representatives with SLE were part of the investigator team. Results The analysis revealed three main themes (i.e., learning how to be open about fatigue, learning to listen to the body, andlearning to accept fatigue ) and six sub-themes (i.e., the search for recognition, legitimization, planning and prioritizing, the body's limits and self-indulgence, adjusting life to comply with resources, andacceptance of dependence ). Conclusion Fatigue is the controlling element in everyday life of women with SLE. Patients try to integrate fatigue into their everyday lives by attempting to control it and meet the challenges of structure and planning. This study indicates a need for clinicians to acknowledge patients' fatigue, including supporting patients' own resources, offering information, and conversation about fatigue, as well as involving patients' relatives.